Implementation of Problem-Based Learning Model to Improve Learning Outcomes in Mathematics Subject - Tiwi Tri Setia Agusti; Elly Sukmanasa; Epon Nurlaela (International Journal of Multi Discipline Science (IJ-MDS), 2023)
This study aims to determine the learning outcomes of grade IV students on the implementation of problem-based learning models in mathematics subjects of operation materials, calculating, adding and subtracting numbers to 1,000. This type of research was a Classroom Action Research consisting of 2 cycles. The subjects of this study were grade IVB students of SDN Julang Bogor City. The data collection technique of learning outcomes used objective tests and analyzed with descriptive percentages. The results of this study showed an improvement in both the learning process, changes in student behaviour, and learning outcomes. The learning process of cycle I with a percentage of 97% then cycle II increased to a percentage of 98%, in the change in behaviour of students cycle I with a percentage of 70%, then cycle II with a percentage of 90% and the results of the completeness of students learning outcomes in cycle I 54% were completed, then cycle II increased by 92% which was complete. All aspects studied had increased from cycle I to cycle II. Thus, it can be concluded that the implementation of the problem-based learning model can improve the learning outcomes of grade IVB students of SDN Julang Bogor City.